Pengaruh Jarak Tanam yan Berbeda dari Garis Pantai di Perairan Desa Oenaek, Kabupaten Kupang, NTT terhadap Tingkat Pertumbuhan dan Kandungan Karaginan pada Rumput Laut (Kappaphycus alvarezii) - Kana, Arifin GD; Salosso, Yuliana; Turupadang, Welem L (Nusa Cendana University, 2024)
For forty-five days, the study was carried out in the waterways of Oenaek Village, West Kupang District, Kupang Regency. Using five treatments and three replicates, the Randomized Group Design (RAK) approach was employed to plant seaweed seedlings at five different distances from the shoreline: fifteen, twenty-five, thirty, forty, and fifty meters. Seaweed growth rate, water quality, and carrageenan content were among the test factors. With a value of 3.1 g%/day, treatment B had the highest daily growth rate according to the data. Tests conducted in the laboratory of Undana's Faculty of Animal Husbandry, Marine and Fisheries revealed that treatment E had the highest carrageenan content, reaching 83.3%, while treatment C had the highest absolute growth, coming in at 142.9 g. In Oenaek Village, Kupang Regency, West Kupang District, the aim of this study was to assess the impact of planting distance from the shoreline on absolute growth and carrageenan content in seaweed (Kappaphycus alvarezii). Keywords: Shoreline, spacing, carrageenan, growth, seaweed